Analisis penerapan tax planning PPh 21 sebagai upaya meningkatkan efisiensi pajak pada Kantor Cabang Utama PT BPR Prisma Dana Manado - Rondonuwu, Priskila Meyvira; Rondonuwu, Sintje; Suwetja, ⁠I Gede (Riset Akuntansi dan Portofolio Investasi, 2025)
This study analyzes the application of tax planning for Income Tax Article 21 (PPh 21) at PT BPR Prisma Dana Manado to identify the most efficient calculation method. Many companies still use administratively simple methods that do not maximize tax savings under the self-assessment system. Using a qualitative case study approach, this research employs interviews, observations, and company documents supported by payroll data. Three PPh 21 calculation methods; net, gross, and gross-up, were compared to assess their impact on employee take-home pay and corporate tax burden. The results show that the company currently applies the gross method, which reduces employee take-home pay and provides no tax-saving benefits. The comparative analysis indicates that the gross-up method offers the highest efficiency, as tax allowances are deductible expenses that reduce taxable income. This method yields a 5.18% tax efficiency improvement. The study concludes that the gross-up method is the most optimal strategy, improving both tax efficiency and employee welfare, and strengthening corporate tax compliance.